Karakteristik Orang Tua Dan Pola Makan Anak Usia Sekolah Dasar Negeri - M. Thonthowi Jauhari (Universitas Gorontalo, 2020)
Abstract Primary school-age children are the age in which children are growing and developing both thinking and emotional abilities. The growth and development of a child are influenced by the intake of good nutrients obtained through dietary adjustments. This study aims to analyze the relationship between parental characteristics (education, employment, and parental income) with the eating patterns of public primary school-age children in East Praya District, Central Lombok Regency. This research is an observational study with a cross-sectional design, data analysis using chi-square, and one way-ANOVA test. The results of this study found that the eating patterns of primary school children were mostly in the sufficient category of 39,3%, and less in the category of 38,1%. P-value <0,05 which means that there is a significant relationship between parental characteristics (education, employment, and parental income) with the eating patterns of public primary school-age children. R square value of 29,0% shows that primary school-age children's eating patterns are influenced by 29,0% of the characteristics of parents (education, employment, and parents income). Parents need to pay attention to the quality of their primary-school-age children's eating patterns in a better direction.AbstrakUsia anak sekolah dasar merupakan usia dimna anak-anak mengalami tumbuh kembang baik kemampuan berfikir maupun emosional. Tumbuh kembang seorang anak dipengaruhi oleh asupan zat gizi yang baik yang diperoleh melalui pengaturan pola makan. penelitian ini bertujuan untuk melihat hubungan antara karakteristik orang tua (pendidikan, pekerjaan, dan pendapatan orang tua) dengan pola makan anak sekolah dasar negeri di kecamatan Praya Timur, kabupaten Lombok Tengah. Penelitian ini merupakan penelitian observasional dengan desain cross sectional, analisis data menggunakan chi square dan uji one way-ANOVA. Hasil penelitian ini didapatkan pola makan anak sekolah dasar sebagian besar dalam kategori cukup 39,3%, dan kategori kurang 38,1%. Nilai p<0,05 yang artinya ada hubungan yang signifikan antara karakteristik orang tua (pendidikan, pekerjaan, dan pendapatan orang tua) dengan pola makan anak sekolah dasar negeri di kecamatan Praya Timur, Kabupaten Lombok Tengah.. Nilai r square 29,0% menunjukkan bahwa pola makan anak sekolah dasar di pengaruhi sebanyak 29,0% oleh karakteristik orang tua (pendidikan, pekerjaan dan pendapatan orang tua). Orang tua perlu memperhatikan kualitas pola makan ana- anak sekolah dasar mereka kearah yang lebih baik.